A Christian View of Humanitarian Intervention. Issue 1 (8th March 2019) - Biggar, Nigel
Abstract: As part of a roundtable on "Balancing Legal Norms, Moral Values, and National Interests, " this essay presents a Christian view of how to think coherently about the relationships between those three elements. Christian monotheism entails the view that there is a given moral order or "natural law, " which comprises basic human goods (or universally objective values) and moral rules for defending and promoting them. This natural law precedes all human, positive law. It follows that, while the authority of positive international law is important for the maintenance of the good of social order, it is still penultimate, since it can be trumped by natural law. Moreover, international law's authority is weaker than that of national law, because controversy over its sources gives greater scope for the interpreter's moral and political prejudices to shape its construal. Since the interpretation of international law is subject to diverse construals, occasions arise when its authority is invoked to shield the perpetration of grave injustice. In such circumstances, an appeal to natural law could supply moral justification for humanitarian military intervention, even when it violates the letter of international law. Humanitarian intervention, however, is often criticized for being motivated by national interests. A Christian view that follows Thomas Aquinas, however, does not regard national interests as immoral per se, but recognizes that self-interest can be legitimate, and that a national government has a moral responsibility to promote the legitimate interests of its people.